2006
DOI: 10.1111/j.0303-6987.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical chronic lymphocytic leukaemia associated with a 13q deletion presenting initially in the skin: apropos of a case

Abstract: This case identifies a cutaneous presentation of subclinical B-CLL. There are two prior reports describing B-CLL presenting initially in the skin. In one case, the infiltrates were incidental on a re-excision specimen. The second report suggests 16% of B-CLL patients have cutaneous manifestations as the first sign of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
(8 reference statements)
1
13
1
Order By: Relevance
“…8,14 Cutaneous B-CLL as the primary manifestation of the disease is unusual, and only a few such manifestations are reported in the medical literature. 2,12,15 The cases discussed herein are presented for the uniqueness of their clinical presentations, clinical features, and variant histopathologic features. In case 1, the helpful histologic clues included the presence of a moderately dense atypical lymphoid infiltrate with significant amount of crush artifact and supportive immunophenotype (coexpression of CD5 and CD23 with k immunoglobulin light chain restriction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,14 Cutaneous B-CLL as the primary manifestation of the disease is unusual, and only a few such manifestations are reported in the medical literature. 2,12,15 The cases discussed herein are presented for the uniqueness of their clinical presentations, clinical features, and variant histopathologic features. In case 1, the helpful histologic clues included the presence of a moderately dense atypical lymphoid infiltrate with significant amount of crush artifact and supportive immunophenotype (coexpression of CD5 and CD23 with k immunoglobulin light chain restriction).…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, cases of B-CLL present subclinically with cutaneous involvement that corresponds to the initial signs of underlying B-CLL. 2,12,15,19 In one study of 42 cases of cutaneous B-CLL, 16.7% (7/42) of the cases presented clinically with cutaneous manifestations as the first sign of disease. 2 Histologic examination of all 42 cases revealed features consistent with specific cutaneous infiltrates of B-CLL.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Prior studies found individuals with a history of SCC to have a 2-fold increased risk of developing CLL, 13 …”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review, smudge cells were prone to be observed in hematological malignancies, especially in chronic lymphocytic leukemia (Heinivaara et al, 1959;Nosanchuk et al, 1979;Paydas et al, 1999;Khandelwal et al, 2006;Carulli et al, 2007), although the presence of smudge cells had been considered as a well-described artifact before because of the rupture of fragile lymphocytes in preparing the peripheral blood smear (Macdonald et al, 2003). It was reported that a remarkable reduction in the percentage of smudge cells was found with the supplement of bovine serum albumin compared with those without (Lunning et al, 2004).…”
Section: Discussionmentioning
confidence: 99%